Climate-change induced tropicalisation of marine communities in Western Australia - Cheung, W.; Meeuwig, J.; Feng, M.; Harvey, Euan; Lam, V.; Langlois, T.; Slawinski, D.; Sun, C.; Pauly, D. (CSIRO Publishing, 2012)
A major observed and predicted impact of climate change on marine species is the poleward shift in their distributions and the resulting changes in community structure. Here, we used a Dynamic Bioclimate Envelope Model to project range shift of exploited marine fishes and invertebrates in Western Australia. We combined published data andexpert knowledge to predict current species distributions for 30 tropical, sub-tropical and temperate species that occur along the coast of Western Australia. Using outputs from both a Regional Oceanographic Model and a Global Circulation Model, we simulated change in the distribution of each species. Our study shows that under the SRES (Special Report forEmission Scenarios) A1B scenario, the median rate of distribution shift is around 19 km decade 1 towards higher latitudes and 9m deeper decade 1 by 2055 relative to 2005. As a result, species gains and losses are expected along the south coast and north coast of Western Australia, respectively. Also, the coast of Western Australia is expected to experience a‘tropicalisation’ of the marine community in the future, with increasing dominance of warmer-water species. Such changes in species assemblages may have large ecological and socio-economic implications through shifts in fishing grounds and unexpected trophic effects.